La aplicación del régimen semiabierto y su eficiencia en la rehabilitación de las personas privadas de la libertad del cantón Guaranda - Miranda Estrada, Christian Javier (2024)
ABSTRACT: The purpose of this research is to analyze the application of the semi-open regime through the review of case studies of persons deprived of liberty in the Guaranda Canton to determine its efficiency in fulfilling the purposes of the sentence and social rehabilitation. Prison benefits respond to a clear line of approach to social rehabilitation and the purposes of the sentence. However, an adequate application of these prison benefits is not always carried out in the reality that the person deprived of liberty lives in the Ecuadorian prison system. The purposes of the social rehabilitation system have been established from the constitutional guidelines proposed in the Montecristi constitution of 2008, in which the integral rehabilitation of criminally sentenced persons is considered to be the purpose of reintegrating them into society, as well as the protection of persons deprived of liberty and the guarantee of their rights. In this sense, the purposes of the sentence also play a leading role within the penitentiary regulations that govern the Ecuadorian system so that with the validity of the Comprehensive Organic Criminal Code, the general prevention of the commission of crimes is established as the purpose of the sentence, as well as the development of the capacities of convicted persons, thus in the norm above it establishes as social rehabilitation regimes: closed, semi-open, open. The legal nature of the semi open regime becomes a penitentiary benefit adapted to the current social rehabilitation system, which will reflect its effectiveness within the persons deprived of their liberty.